PEMBERDAYAAN SISWA PONDOK PESANTREN MADRASAH ALIYAH SWASTA MU’ALLIMIN TEMANGGUNG DENGAN TEKNOLOGI TEPAT GUNA OPEN PAN DRYING DALAM PENGOLAHAN SUSU KAMBING BERNILAI EKONOMIS - Dian Juliani; Endah Wening Budiningrum; Citra Purwita; Wawan Setyawan Suprayogi; Hisyam Azzam Akbar; Riska Damayanti (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
The Muallimin Temanggung Private Islamic Boarding School has great potential in goat milk processing, but so far it has not been optimally utilized. To address this challenge, the objective of this empowerment program is to apply appropriate open pan drying technology to process liquid goat milk into powdered milk that is more durable and has a high selling value, while also improving the entrepreneurial skills of the students. The methods used included delivering material on entrepreneurial motivation, financial literacy, and digital marketing, as well as hands-on training in goat milk processing, storage, packaging, and food safety standards. The pretest results showed that the students' knowledge was still low, averaging 2.75–3.45, especially in processing techniques and BPOM standards. After the training, the post-test results increased significantly, with an average of 3.35–4.05, including an understanding of the processing of milk powder and good packaging techniques. The conclusion of this community service activity is that the application of open pan drying has proven to be effective in processing goat milk into quality products and is able to improve the skills, motivation, and entrepreneurial intention of santri.